THE REACTION OVER EMPLOYEES PERFORMANCE THROUGH ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT VARIABLES WHOM MEDIATED BY ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AND ITS IMPLICATIONS AT PT SHARPRINDO DINAMIKA PRIMA - Sutrisno, Dadan; Chaeruddin (Dinasti International Journal of Management Science, 2020)
This research aims to inspects the reaction between Organizational Culture, Organizational Commitment and Organizational Citizenship Behavior also its implications to Employees Performance at PT Sharprindo Dinamika Prima Tangerang. By using 100 employees at PT Sharprindo Dinamika Prima as respondents, and samples would taking with using a random sampling design proportional strata. The Data has been processed by SmartPLS SEM Version 3.0. The results of this research was indicated that Organizational Culture has strong reaction towards Employees Performance, Organizational Commitment has strong reaction over Employee Performance, Organizational Citizenship Behavior has strong reactions over Employee Performance, the outcome from this research simultaneously shows that the Organizational Culture, Organizational Commitment and Organizational Citizenship Behavior simultaneously has positive react kon employee performance